The Effects of High Performance Work Practices on Job Satisfaction in the United States Steel Industry - Berg, Peter (Relations industrielles / Industrial Relations, 1999)
A unique data set is used to examine how different practices associated with high performance work Systems in the steel industry affect the job satisfaction of workers. While the effect of these practices on organizational performance is widely studied, few have examined their effects on workers. The analysis in this paper is based on data from a sample of 1,355 hourly workers in the U.S. steel industry across 13 plants. The results indicate that the effect of high performance work practices on job satisfaction dépends primarily on how work roles and job duties are defined, on good employee-management relations and on practices that help balance work and family responsibilities. These results show that those who are able to use their skills and knowledge on the job, those who report positive employée-management relations, and those who believe the company helps them balance work and family responsibilities have relatively high probabilities of being very satisfied with their jobs.